2012
DOI: 10.4102/sajbm.v43i3.475
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of corporate entrepreneurship

Abstract: Businesses should strive to identify and nurture internal organisational factors that cultivate a dynamic entrepreneurial culture. This paper scrutinizes the contribution of the internal organisational factors, measured by market orientation, flexibility and job satisfaction, to intrapreneurship, as measured by the Corporate Entrepreneurship Assessment Instrument (CEAI). Information from a sample of 333 managers explores the relationships of corporate entrepreneurship with different work variables by means of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 91 publications
2
38
0
2
Order By: Relevance
“…For example, while employees were cognizant of how rewards were linked to their entrepreneurial efforts, promotion and nonfinancial rewards such as recognition for a job done well were most valued, and employees respected the need for compliance behavior. Ideas of compliance and deference are orthogonal to our knowledge of what entrepreneurship in SMEs requires, and we add empirical evidence to a group of studies that collectively reveal the problems of deference to authority (e.g., Beugr e and Offodile 2001; Jackson, Kenneth, and Serap 2008;Kamoche 2011;van Wyk and Adonisi 2012). In our case firms, that deference to authority even overruled a cultural expectation of obedience of managerial instructions.…”
Section: Discussion and Contributionsmentioning
confidence: 83%
See 1 more Smart Citation
“…For example, while employees were cognizant of how rewards were linked to their entrepreneurial efforts, promotion and nonfinancial rewards such as recognition for a job done well were most valued, and employees respected the need for compliance behavior. Ideas of compliance and deference are orthogonal to our knowledge of what entrepreneurship in SMEs requires, and we add empirical evidence to a group of studies that collectively reveal the problems of deference to authority (e.g., Beugr e and Offodile 2001; Jackson, Kenneth, and Serap 2008;Kamoche 2011;van Wyk and Adonisi 2012). In our case firms, that deference to authority even overruled a cultural expectation of obedience of managerial instructions.…”
Section: Discussion and Contributionsmentioning
confidence: 83%
“…An emerging economy context holds very different institutional characteristics compared to the traditional Western origin of CE studies. For example, a collectivist culture, authoritarianism, and deference to authority prevalent in African nations can shape indifference toward entrepreneurship among African employees (Jackson, Kenneth, and Serap 2008;Morris, Davis, and Allen 1994;van Wyk and Adonisi 2012). Institutional differences and institution-specific conditions can also directly affect strategic choices available at the level of the emerging economy firm (Young et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This variable has been widely mentioned in the literature regarding intrapreneurship, therefore there is evidence that, depending on the sector, free time may be related to intraprenurial behavior, or not, for example, Alpkan et al (2010) found that in manufacturing sectors free time resulted counterproductive. However, other researches demonstrate the opposite (Hornsby et al, 2013;Kuratko et al, 2014;Van Wyk and Adonisi, 2012). Concerning the software sector, M. Trujillo said that at leat at Amazon, free time for employees is one of their strategies (personal communication, November 14 th 2018) and P.E.…”
Section: Intrapreneurship Organizational Factors: Real Variablesmentioning
confidence: 99%
“…In the literature, the administrative support variable has been present as an organizational factor of great importance in the development of internal entrepreneurship (eg. Alpkan et al, 2010;Hornsby et al, 2013;Moriano et al, 2011;Rutherford and Holt, 2007;Srivastava and Agrawal, 2010;Van Wyk and Adonisi, 2012), administrative support is identified as the senior officers' will to promote intrapreneurship, including also the support to the innovative ideas coming from the employees, as well as the adequate management of resources so that they are accomplished (Kuratko et al, 2005;Kuratko et al, 2014;Moriano et al, 2011).…”
Section: Intrapreneurship Organizational Factors: Real Variablesmentioning
confidence: 99%
“…In this condition, CE can be established as a strategy that can be adopted to ensure the success of contractor businesses. However, van Wyk and Adonisi [6] mentioned that the model of CE cannot be generalized to all business sectors, therefore, the specific model of CE for contractor businesses needs to be explored in a specific way. Comparing to other companies, contractors run their business in a unique way.…”
Section: Introductionmentioning
confidence: 99%